Graphene coolant with reversible recovery performance and preparation method thereof
Patent Information
- Application Number
- CN202611072965.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明的目的在于提供一种具有可逆恢复性能的石墨烯冷却液及其制备方法,以解决现有石墨烯冷却液中存在的石墨烯易不可逆团聚、分散稳定性差、导热增强与粘度增长难以兼顾、分散剂用量高、界面热阻大以及商品化石墨烯粉体成本较高等实际应用的瓶颈问题
[0030]1、制备方法具有原位剥离和复合分散协同优势:与传统外加商品化石墨烯粉体、强氧化改性或大量分散剂稳定的方法相比,本发明通过在冷却液基液中对大片径石墨颗粒(<80目)进行超声空化破碎和原位剥离,在生成石墨烯纳米片的同时使分散剂能够快速吸附并覆盖新鲜裸露的片层表面,实现石墨烯在冷却液中的同步生成和同步分散,从而降低了石墨烯组分的再分散难度和片层不可逆团聚风险。与现有方法中先制备石墨烯粉体、再经清洗、干燥和分散的技术路线相比,本发明直接在目标冷却液体系中原位剥离生成石墨烯纳米片,不需预先制备石墨烯原浆,而是在目标冷却液基液中完成石墨原位剥离、碳纳米管复合分散和后稳定处理,可显著减少中间处理过程,降低制备成本,并避免强氧化或重度化学接枝对石墨烯共轭结构的破坏,有利于保留石墨烯片层的本征导热能力和较大有效片径,为冷却液中导热通路的构筑提供基础。
Smart Images

Figure CN122958992A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermally conductive functional materials and liquid cooling heat dissipation media, specifically a graphene coolant with reversible recovery properties and its preparation method. Background Technology
[0002] With the increasing power density of high-power electronic devices, data center servers, power batteries, energy storage systems, medical equipment, and industrial equipment, traditional air cooling methods are no longer sufficient to meet the heat dissipation requirements under high heat flux density conditions. Liquid cooling technology, due to its advantages such as high heat exchange efficiency, stable temperature control, low noise, and compact structure, has gradually become an important technical approach for thermal management of high-power equipment. Among these factors, the thermal conductivity, flow properties, antifreeze properties, dispersion stability, and long-term reliability of the liquid cooling medium are key factors affecting the overall heat dissipation efficiency and operational safety of the liquid cooling system.
[0003] Graphene, with its high in-plane thermal conductivity, high specific surface area, and excellent two-dimensional sheet structure, is an ideal nanofiller for improving the thermal conductivity of liquids. However, graphene is prone to agglomeration and sedimentation in base liquids such as water, ethylene glycol / water, or propylene glycol / water due to van der Waals interactions. Existing graphene nanofluids typically rely on strong oxidative modification, chemical grafting, and large amounts of surfactants or polymeric dispersants to achieve stable dispersion. For example, patent application CN116750755A discloses a method for preparing a graphene dispersion, which involves reducing graphene oxide, mixing it with a dispersant, and then ultrasonically treating it to obtain the graphene dispersion; patent application CN121674036A discloses a graphene coolant for liquid cooling radiators, which improves the static thermal conductivity of the coolant by using hydroxylated modified graphene; patent application CN109384219A discloses a nanofluid for high-efficiency heat exchange working fluids and its preparation method, which obtains graphene slurry by in-situ liquid phase exfoliation of expanded graphite, and then dilutes the slurry to obtain the nanofluid; patent application CN119823728A discloses a coolant technology solution containing thermally conductive components such as graphene, carbon nanotubes, and nano-alumina, which improves the thermal conductivity of the coolant by compounding various thermally conductive fillers.
[0004] The above technical solutions indicate that graphene dispersions, graphene nanofluids, and graphene composite coolants have been studied and applied. However, existing technologies mainly focus on the dispersion of graphene oxide or modified graphene, secondary dilution and dispersion after graphene slurry preparation, external compounding of pre-made thermally conductive fillers, and improvement of initial thermal conductivity. Such methods still have certain limitations in practical liquid cooling applications: (1) Strong oxidation or chemical modification will destroy the conjugated structure of graphene and reduce its intrinsic thermal conductivity; (2) A large amount of dispersant coating will increase the interfacial thermal resistance between graphene and the base liquid and lead to a significant increase in the viscosity of the system, thereby increasing the power consumption of the operating pump in practical applications; (3) Pre-made graphene powder or modified graphene is prone to sheet stacking during drying, storage, and secondary dispersion, making it difficult to rewet and uniformly disperse in the coolant. There is still room for improvement in existing technologies regarding the simultaneous in-situ exfoliation and composite dispersion of graphite raw materials directly in the target coolant base liquid, as well as the ability to redisperse and restore thermal conductivity when the coolant settles, softly agglomerates, or separates after long-term static storage, thermal cycling, pumping shearing, or vibration.
[0005] Furthermore, existing graphene coolants typically aim for "long-term, completely stable dispersion." However, in actual liquid cooling systems, the coolant is constantly subjected to pumping, shearing, vibration, and temperature changes, and the system does not necessarily need to maintain a static, completely suspended state at all times. For closed-loop liquid cooling systems, it is more important that the coolant, after settling, soft agglomeration, or stratification, can regain uniform dispersion under external forces while maintaining its thermal conductivity and flow properties. Therefore, developing a graphene coolant with "reversible recovery properties," allowing it to form redispersible soft agglomerates when stationary and recover its properties after stirring, pumping, or agitation, has significant practical application value. Summary of the Invention
[0006] The purpose of this invention is to provide a graphene coolant with reversible recovery properties and its preparation method, so as to solve the bottleneck problems in practical applications of existing graphene coolants, such as graphene's easy irreversible agglomeration, poor dispersion stability, difficulty in balancing thermal conductivity enhancement and viscosity increase, high dispersant dosage, large interfacial thermal resistance, and high cost of commercial graphene powder.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] A method for preparing a graphene coolant with reversible recovery properties includes the following steps:
[0009] The stripping agent and carbon nanotubes were added to the coolant base liquid, and after stirring and dispersion homogenization, a uniform dispersion was obtained.
[0010] Graphite raw material is added to the uniform dispersion liquid, and after stirring and dispersion homogenization treatment, the graphite raw material is directly exfoliated in situ in the cooling liquid base liquid to form graphene nanosheets, and at the same time, the graphene nanosheets and carbon nanotubes form a graphene-carbon nanotube composite dispersion system in the cooling liquid base liquid.
[0011] Inorganic nano-auxiliaries and dispersants are added to the graphene-carbon nanotube composite dispersion system, and after stirring and dispersion homogenization, a graphene coolant with reversible recovery properties is obtained. The inorganic nano-auxiliaries are used as layer spacer components or reversible enrichment layer structure regulating components, and improve the interfacial wetting and thermal coupling between the composite dispersion system and the coolant base liquid.
[0012] The reversible recovery performance refers to the ability of the graphene coolant to reform into a uniform dispersion system after settling, stratification, or soft agglomeration under the action of mechanical external force, and the thermal conductivity recovery rate of the redispersed graphene coolant calculated according to the thermal conductivity enhancement recovery rate is not less than 99.0%.
[0013] Furthermore, the coolant base is a water mixture solution of one or more of ethylene glycol, propylene glycol, glycerin, diethylene glycol, and triethylene glycol.
[0014] Furthermore, the graphite raw material is one or more of expandable graphite, expanded graphite, and flake graphite, with a mesh size <80 mesh and a carbon content >99%; the amount of graphite raw material added accounts for 0.05-5.0 wt% of the total mass of the graphene coolant; the carbon nanotubes are one or more of multi-walled carbon nanotubes and functionalized carbon nanotubes, with an outer diameter distribution of 5-20 nm, a carbon tube length of 1-30 μm, and a carbon content >99%; the amount of carbon nanotubes added accounts for 0.001-0.5 wt% of the total mass of the graphene coolant.
[0015] Furthermore, the stripping agent is one or more of the following: sodium pyrene tetrasulfonate, sodium diisobutylnaphthalene sulfonate, tannic acid, octylphenol polyoxyethylene ether, polysorbate, fatty alcohol polyoxyethylene ether, and acetylenol wetting agents; the dispersing agent is one or more of the following: polyvinylpyrrolidone, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, branched polyester, polyvinyl alcohol, polyacrylate, sodium naphthalene sulfonate formaldehyde polymer, quaternary ammonium salt polymer, and block polyether dispersants; the amount of the stripping agent and the dispersing agent added is independently 0.001-2.5 wt% of the total mass of the graphene coolant.
[0016] Furthermore, the inorganic nano-additive is one or more of nano-silica, nano-alumina, nano-boron nitride, nano-magnesium oxide, nano-zinc oxide, nano-copper oxide, and nano-titanium dioxide; the amount of the inorganic nano-additive is 0.001-1.0 wt% of the total mass of the graphene coolant; the inorganic nano-additive is added after the graphene-carbon nanotube composite dispersion system is formed and distributed between graphene nanosheets or in the graphene-carbon nanotube composite structure, which is used to reduce the density of the graphene nanosheets and keep the enriched structure formed after standing in a redispersible state; at the same time, it improves the interfacial wetting and thermal coupling between the composite dispersion system and the coolant base liquid, and improves the effective thermal conductivity of the near-wall region of the cold plate.
[0017] Furthermore, the dispersion homogenization process is independently one or more of ultrasonic homogenization, high-pressure homogenization, microfluidic treatment, cell disruption homogenization, or sand milling homogenization.
[0018] The ultrasonic homogenizer has a power of 0.2-5.0 kW, an ultrasonic frequency of 10-60 kHz, and an ultrasonic energy input of not less than 0.005-0.1 kWh / L.
[0019] The working pressure of the high-pressure homogenizer is 60-150 MPa, and the cycle is 1-20 times.
[0020] The working pressure of the microjet treatment is 30-250 MPa, and the treatment is repeated 1-15 times.
[0021] The working pressure for cell disruption and homogenization is 20-180 MPa, and the process is repeated 1-15 times.
[0022] The grinding media used in the sand milling process has a particle size of 0.05-1.0 mm, a grinding media filling rate of 50%-90%, a rotation speed of 1000-5000 rpm, and a processing time of 10-180 min.
[0023] The system operating temperature during the dispersion and homogenization process shall not exceed 60℃.
[0024] Furthermore, the preparation method also includes a static grading step; the static grading step includes: allowing the graphene coolant to stand, so that the system forms an upper stable dispersion layer and a lower reversible enrichment layer, separating and taking the upper stable dispersion layer to obtain a stable dispersion graphene coolant; the static grading time is 8-48 h; the lower reversible enrichment layer is a soft agglomerate or redispersible enrichment structure containing graphene nanosheets, carbon nanotubes, inorganic nano-auxiliaries and dispersing agents.
[0025] Furthermore, after the lower reversible enrichment layer is recombined with all the separated upper stable dispersion layers, it is stirred, oscillated or circulated and pumped to restore the appearance of a uniform dispersion system with the same composition as before static grading; the thermal conductivity recovery rate of the redispersed system calculated according to the thermal conductivity enhancement recovery rate is not less than 99.0%.
[0026] Another object of the present invention is to provide a graphene coolant with reversible recovery properties prepared by the above preparation method.
[0027] Another object of the present invention is to provide an application of the above-mentioned graphene coolant as a liquid cooling heat dissipation medium.
[0028] This invention provides a method for preparing a graphene coolant with reversible recovery properties. The method involves using ultrasonic and other dispersion homogenization techniques to drive the in-situ exfoliation of graphite into graphene nanosheets within a coolant base. Carbon nanotubes, inorganic nano-auxiliaries, and dispersing agents are then combined to construct a composite dispersed thermally conductive structure with reversible recovery properties. After sedimentation, stratification, or soft agglomeration, the resulting graphene coolant can be restored to a uniform dispersion state through gentle stirring, oscillation, or circulating pumping, while essentially maintaining its original thermal conductivity and rheological properties. This invention effectively solves the bottleneck problems in practical applications of nanofluids, such as the difficulty in balancing enhanced thermal conductivity and viscosity growth, poor dispersion stability, susceptibility to irreversible agglomeration, difficulty in redispersing commercial graphene powder, and high cost. The graphene coolant prepared by this invention is suitable for non-insulating liquid cooling heat dissipation scenarios in electronic devices, industrial equipment, cold plate heat exchangers, and closed-loop circulating liquid cooling systems.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] 1. The preparation method has the synergistic advantages of in-situ exfoliation and composite dispersion: Compared with the traditional method of adding commercial graphene powder, strong oxidation modification or stabilization with a large amount of dispersant, the present invention performs ultrasonic cavitation crushing and in-situ exfoliation of large-diameter graphite particles (<80 mesh) in a coolant base liquid. At the same time as generating graphene nanosheets, the dispersant can be quickly adsorbed and covered on the fresh exposed sheet surface, realizing the synchronous generation and dispersion of graphene in the coolant. This reduces the difficulty of redispersing graphene components and the risk of irreversible agglomeration of sheets. Compared with existing methods that first prepare graphene powder and then clean, dry and disperse it, this invention directly exfoliates graphene nanosheets in situ in the target coolant system. It does not require the pre-preparation of graphene slurry, but completes the in-situ exfoliation of graphite, carbon nanotube composite dispersion and post-stabilization treatment in the target coolant base liquid. This can significantly reduce intermediate processing steps, reduce preparation costs, and avoid the damage to the conjugated structure of graphene caused by strong oxidation or heavy chemical grafting. It is beneficial to retain the intrinsic thermal conductivity and large effective sheet size of graphene sheets, and provides a basis for the construction of thermal conductivity pathways in the coolant.
[0031] 2. Constructing a reversible and recoverable composite heat-conducting channel improves the system's thermal conductivity and heat transfer capacity: This invention constructs a reversible and recoverable composite heat-conducting channel through the synergistic use of graphene nanosheets, carbon nanotubes, and inorganic nano-auxiliaries. The larger-diameter graphene nanosheets formed by in-situ exfoliation provide a highly thermally conductive two-dimensional channel. Carbon nanotubes act as bridges, supports, and connects between graphene layers. Inorganic nano-auxiliaries serve as layer spacers and structural control components, reducing the degree of graphene layer stacking and improving the composite dispersion structure. Compared with the preparation methods and performance of single graphene nanofluids reported in most papers, this invention uses two-dimensional graphene, one-dimensional carbon nanotubes, and particulate inorganic nano-auxiliaries to form a complementary relationship in spatial structure and heat transfer path. This is beneficial for improving the thermal conductivity of the coolant and the circulating heat transfer capacity of the cold plate, and enables the heat-conducting channel to possess dynamic recovery characteristics that allow for destruction and reconstruction under static and external force conditions.
[0032] 3. It exhibits low viscosity growth, reversible recovery, and long-term operational stability, making it suitable for practical liquid cooling conditions: Compared to techniques that directly increase the content of nanofillers or add more dispersants, this invention, through the synergistic effect of low-dose dispersing agents, in-situ exfoliation of graphene, and composite thermally conductive structures, improves thermal conductivity while controlling viscosity growth. This reduces flow resistance of the coolant in cold plates, pipes, and heat exchangers, thus lowering energy consumption for circulating pumps. Furthermore, even if the resulting graphene coolant undergoes sedimentation, stratification, or soft agglomeration during settling, it can be restored to a uniformly dispersed state and its thermal conductivity restored through gentle stirring, oscillation, or circulating pumping. Compared to similar commercial coolants and existing nanofluid preparation techniques, this invention not only focuses on improving initial thermal conductivity but also considers viscosity changes, dynamic heat transfer capacity, redispersibility after settling, and long-term operational reliability. It better suits the actual operating environment of closed-loop circulating liquid cooling systems, which involves long-term pumping, shearing, vibration, and temperature changes, thus extending coolant lifespan and improving system operational stability. Attached Figure Description
[0033] Figure 1 This is a schematic flowchart illustrating the preparation method of the graphene coolant with reversible recovery properties provided in this embodiment of the invention.
[0034] Figure 2 The image shows the AFM test pattern of the multilayer graphene nanosheets in the graphene coolant obtained in the embodiment of the present invention (average thickness is about 20 nm).
[0035] Figure 3 This is a schematic diagram of the reversible recovery performance of the graphene coolant obtained in this invention; in the figure, (1) is the initial dispersion stage, which is uniformly dispersed; (2) is a schematic diagram of the upper stable dispersion layer and the lower reversible enrichment layer after standing; (3) is the redispersion state after manual pouring. Detailed Implementation
[0036] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0037] like Figure 1 As shown, in one embodiment of the present invention, a method for preparing a graphene coolant with reversible recovery properties is provided, comprising the following steps:
[0038] S1. Add the stripping agent and carbon nanotubes (CNTs) to the coolant base liquid, and after stirring and dispersing homogenization, the carbon nanotubes are unentangled and dispersed in the coolant base liquid to obtain a uniform dispersion.
[0039] S2. Add graphite raw material (i.e. graphite powder) to the above uniformly dispersed liquid. After stirring and dispersing homogenization, the graphite raw material is directly crushed and peeled in situ in the cooling liquid base to form graphene nanosheets. At the same time, the graphene nanosheets and carbon nanotubes form a graphene-carbon nanotube composite dispersion system containing a graphene-carbon nanotube composite structure in the same cooling liquid base.
[0040] S3. Add inorganic nano-auxiliaries and dispersing agents to the above graphene-carbon nanotube composite dispersion system. After stirring and homogenizing, the inorganic nano-auxiliaries are distributed between graphene nanosheets or in the graphene-carbon nanotube composite structure, and the dispersing agents are adsorbed or entangled on the surface of graphene nanosheets and carbon nanotubes, thus obtaining a graphene coolant with reversible recovery properties.
[0041] It should be noted that reversible recovery performance refers to the ability of graphene coolant to reform into a uniform dispersion system after settling, stratification, or soft agglomeration under mechanical external force (such as stirring, oscillation, or circulating pumping), with a thermal conductivity recovery rate calculated based on thermal conductivity enhancement recovery rate of not less than 99.0%.
[0042] This invention relates to a method for directly exfoliating graphite raw materials in a coolant base liquid using ultrasonic in-situ, thereby exfoliating graphite into graphene nanosheets within the coolant system. Simultaneously, carbon nanotubes are introduced as a one-dimensional bridging component, forming a supporting and connecting structure between the graphene sheets, inhibiting the overlap and dense re-stacking of graphene nanosheets. Through the synergistic effect of exfoliation and dispersing agents, the wetting and exfoliation efficiency of graphite powder and the reversible dispersion performance of the graphene / carbon nanotube (CNT) composite system are improved. Furthermore, inorganic nano-agents are used as rigid spacers to regulate the system's microstructure, maintaining a loose and redispersible structure in the reversibly enriched layer and improving interfacial thermal coupling in the near-wall region of the metal cold plate, resulting in a graphene coolant with excellent reversible recovery properties.
[0043] In a preferred embodiment of the present invention, the coolant base is a water mixture solution of one or more of ethylene glycol, propylene glycol, glycerin, diethylene glycol, and triethylene glycol.
[0044] The graphite raw material is one or more of expandable graphite, expanded graphite, and flake graphite, with a mesh size <80 mesh (e.g., 20-80 mesh) and a carbon content >99% (preferably >99.9%). The amount of graphite raw material added accounts for 0.05-5.0 wt% (preferably 0.5-3.0 wt%) of the total mass of the graphene coolant. The carbon nanotubes are one or more of multi-walled carbon nanotubes and functionalized carbon nanotubes, with an outer diameter distribution of 5-20 nm, a carbon tube length of 1-30 μm (preferably 10-30 μm), and a carbon content >99% (preferably >99.5%). The amount of carbon nanotubes added accounts for 0.001-0.5 wt% (preferably 0.05-0.3 wt%) of the total mass of the graphene coolant.
[0045] The stripping agent is one or more of the following: sodium pyrene tetrasulfonate, sodium diisobutylnaphthalene sulfonate, tannic acid, octylphenol polyoxyethylene ether, polysorbate, fatty alcohol polyoxyethylene ether, and acetylenol wetting agents; the dispersing agent is one or more of the following: polyvinylpyrrolidone, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, branched polyester, polyvinyl alcohol, polyacrylate, sodium naphthalene sulfonate formaldehyde polymer, quaternary ammonium salt polymer, and block polyether dispersants; the amount of stripping agent and dispersing agent added is independently 0.001-2.5 wt% of the total mass of the graphene coolant; preferably, the amount of stripping agent added is 0.02-0.2 wt% of the total mass of the graphene coolant; and the amount of dispersing agent added is 0.02-0.3 wt% of the total mass of the graphene coolant.
[0046] The inorganic nano-additive is one or more of nano-silica, nano-alumina, nano-boron nitride, nano-magnesium oxide, nano-zinc oxide, nano-copper oxide, and nano-titanium dioxide. The amount of inorganic nano-additive added accounts for 0.001-1.0 wt% (preferably 0.01-0.5 wt%) of the total mass of the graphene coolant. The inorganic nano-additive is used as a layer spacer component or a reversible enrichment layer structure regulating component. It is added after the graphene-carbon nanotube composite dispersion system is formed and distributed between graphene nanosheets or in the graphene-carbon nanotube composite structure. It is used to reduce the density of the graphene nanosheets and keep the enriched structure formed after standing in a redispersible state. At the same time, it improves the interfacial wetting and thermal coupling between the composite dispersion system and the coolant base liquid, and improves the effective thermal conductivity of the near-wall region of the cold plate.
[0047] The dispersion homogenization treatment in each of the above steps is independently one or more of the following: ultrasonic homogenization, high-pressure homogenization, microfluidic treatment, cell disruption homogenization, or sand milling homogenization. Specifically, the ultrasonic homogenization power is 0.2-5.0 kW (preferably 1.0-3.0 kW), the ultrasonic frequency is 10-60 kHz (preferably 10-30 kHz), and the ultrasonic energy input is not less than 0.005-0.1 kWh / L; specifically, the ultrasonic energy input in step S1 is not less than 0.01 kWh / L (preferably 0.1-0.5 kWh / L); the ultrasonic energy input in step S2 is not less than 0.1 kWh / L (preferably 0.5-2.0 kWh / L); and the ultrasonic energy input in step S3 is not less than 0.005 kWh / L (preferably 0.02-0.5 kWh / L). The high-pressure homogenization operates at a pressure of 60-150 MPa and is cycled 1-20 times (preferably 3-10 times). The working pressure of the microfluidic treatment is 30-250 MPa (preferably 80-180 MPa), and the treatment is repeated 1-15 times (preferably 2-8 times). The working pressure of cell disruption and homogenization is 20-180 MPa (preferably 60-150 MPa), and the treatment is repeated 1-15 times (preferably 2-8 times). The particle size of the grinding media in the sand milling treatment is 0.05-1.0 mm (preferably 0.1-0.5 mm), the filling rate of the grinding media is 50%-90% (preferably 60%-80%), the rotation speed is 1000-5000 rpm (preferably 1500-3500 rpm), and the treatment time is 10-180 min (preferably 30-120 min). The system working temperature during the dispersion and homogenization treatment does not exceed 60℃ (preferably 10-40℃).
[0048] In a preferred embodiment of the present invention, the above preparation method further includes a static grading step: the graphene coolant is allowed to stand, allowing the system to form an upper stable dispersion layer and a lower reversible enrichment layer; the upper stable dispersion layer is then separated and taken to obtain a stable dispersion graphene coolant; wherein the static grading time is 8-48 h; the lower reversible enrichment layer is a soft agglomerate or redispersible enrichment structure containing graphene nanosheets, carbon nanotubes, inorganic nano-auxiliaries, and dispersing agents. After the lower reversible enrichment layer is recombined with all the separated upper stable dispersion layers, it is stirred, oscillated, or circulated by a pump to restore a uniform dispersion system with the same composition as before static grading; the thermal conductivity recovery rate of the redispersible system, calculated by the thermal conductivity enhancement recovery rate, is not less than 99.0%.
[0049] In this embodiment of the invention, graphite raw materials can be directly crushed and exfoliated in situ in a target coolant base to form graphene nanosheets, which then form a composite dispersion structure with carbon nanotubes in the same coolant base system. Simultaneously, an exfoliation aid promotes graphite wetting and exfoliation, a dispersing aid enhances the reversible dispersion capability of the graphene-carbon nanotube composite system, and inorganic nano-additives regulate the interlayer spacing of graphene sheets, the microstructure of the reversible enrichment layer, and interfacial wetting and thermal coupling. This results in a graphene coolant that exhibits enhanced thermal conductivity, low viscosity increase, and redispersibility after standing. The results show that the obtained graphene coolant has a 10.2-31.6% higher thermal conductivity than the same ethylene glycol / water coolant base, and a 20.2-51.3% higher convective heat transfer coefficient under the same cold plate circulating heat exchange conditions. After standing at room temperature for 30 days and then redispersing, the thermal conductivity recovery rate exceeds 99%, while the viscosity remains essentially unchanged, demonstrating excellent reversible dispersion recovery performance and thermal conductivity.
[0050] Unless otherwise specified, all raw materials used in the following embodiments are commercially available products and can be purchased through commercial channels. The invention will be described in detail below through specific embodiments in practical applications.
[0051] For example, in the following embodiments, unless otherwise specified, the graphite raw material used is expanded graphite with a mesh size of 20-80 mesh and a carbon content >99.9%; the carbon nanotubes used are multi-walled carbon nanotubes with an outer diameter distribution of 5-20 nm, a length of 10-30 μm, and a carbon content >99.5%; the coolant base liquid used is ethylene glycol and water in a mass ratio of ethylene glycol:water = 54:46, with a freezing point of -40℃, a thermal conductivity of 0.3985 W / (m·K), and a viscosity of 2.78 mPa·s. All samples were tested at 25℃.
[0052] The testing methods used for the performance of graphene coolant are as follows:
[0053] 1. Thermal conductivity test: Before the test, the coolant sample was gently shaken or stirred at low speed to restore the system to a uniform dispersion state. Then, the thermal conductivity was measured using a hot-wire method liquid thermal conductivity meter. Each sample was tested in parallel 5 times, with a 3-minute interval between each test. The average value was taken as the thermal conductivity of the sample.
[0054] 2. Reversible Recovery Performance Test: The graphene coolant was allowed to stand at room temperature for 30 days. After standing, the sample was mechanically stirred at 100-200 rpm for 5-10 min, manually shaken for 10-60 s, or circulated by a pump for 1-10 min to redisperse the sedimentation layer, concentration gradient, or soft agglomerates formed during the standing process. Its thermal conductivity was then measured. The reversible dispersion recovery performance was evaluated by comparing the change in thermal conductivity between the initial thermal conductivity and the thermal conductivity after standing and redispersion.
[0055] Thermal conductivity recovery rate = (k 静置再分散 -k 基液 ) / (k 初始 -k 基液 )×100%;
[0056] Where, k 初始 The thermal conductivity, k, of the freshly prepared graphene coolant. 静置再分散 The thermal conductivity, k, is the value of the graphene coolant after it has been allowed to stand and redispersed uniformly. 基液 This is the thermal conductivity of the coolant base fluid (ethylene glycol and water coolant), expressed in W / (m·K).
[0057] 3. Viscosity test: The dynamic viscosity of the graphene coolant at 25 °C was tested using a rotational rheometer, and the unit is mPa·s.
[0058] 4. Calculation of Ultrasonic Energy Input: The ultrasonic energy input is calculated based on the output power of the ultrasonic homogenizer, the ultrasonic time, and the volume of the liquid being treated. Specifically:
[0059] Ultrasonic energy input = power of ultrasonic homogenizer × ultrasonic time / volume of ultrasonic liquid;
[0060] 5. Heat Transfer Performance Test: The convective heat transfer performance of the graphene coolant under laminar flow conditions was evaluated using a cold plate circulating heat transfer test device. The cold plate used in the test was made of aluminum alloy, with a single channel width of 3.0 cm and a height of 0.4 cm. Four channels were connected in parallel, with an effective heat transfer area of 0.1 m². 2During testing, ethylene glycol / water coolant or graphene coolant were added to the same closed-loop heat exchange system, respectively, under conditions of heating power of 300-1000 W, inlet water temperature of 25 ℃, and mass flow rate of 5.0 kg / min. After the system reached a stable heat exchange state, the convective heat transfer coefficients of the same ethylene glycol / water coolant and graphene coolant were measured, and the improvement rate of the convective heat transfer coefficient was calculated using the following formula:
[0061] Convection heat transfer coefficient improvement rate = (h 石墨烯冷却液 -h 基液 ) / h 基液 ×100%;
[0062] Among them, h 石墨烯冷却液 h represents the convective heat transfer coefficient of the graphene coolant under the same test conditions described above. 基液 The convective heat transfer coefficients of the same coolant base fluids (ethylene glycol and water coolant) under the same test conditions described above; the unit is W / (m³). 2 ·K).
[0063] 6. Zeta Potential Test: After restoring the graphene coolant sample to a homogeneous state through gentle agitation or low-speed stirring, a suitable amount of sample was diluted with the same ethylene glycol / water coolant base to a suitable concentration for testing. The Zeta potential was measured using a nanoparticle size and Zeta potential analyzer. The unit is mV. The sample was diluted 20 times during the test, and the test temperature was 25 ℃. A higher absolute value of the Zeta potential indicates a stronger electrostatic repulsion or interfacial stabilization effect between dispersed particles in the system, and can be used as an auxiliary indicator for evaluating the dispersion stability of the system.
[0064] Example 1: This example illustrates that polysorbate 80 and hydroxypropyl methylcellulose can be used for in-situ exfoliation and dispersion of graphite, and that nano-alumina can be used as an inorganic nano-additive for structural regulation of composite thermal conductive systems.
[0065] 0.2 g of polysorbate 80 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 10 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 5.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 30 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.1 g of nano-alumina and 0.5 g of hydroxypropyl methylcellulose were added to the obtained system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0066] The thermal conductivity of the graphene coolant was measured to be 0.4391 W / (m·K), and the viscosity was 2.86 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4389 W / (m·K), and the viscosity was 2.85 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4388 W / (m·K), and the viscosity was 2.84 mPa·s. The obtained graphene coolant showed an increase in thermal conductivity of approximately 10.2% and an increase in viscosity of approximately 2.8%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 99.3%. Furthermore, the absolute value of the Zeta potential of the graphene coolant obtained in this embodiment was measured to be 45.0 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The convective heat transfer coefficient of the obtained graphene coolant under laminar flow conditions was increased by about 20.2% compared with the same ethylene glycol / water coolant base liquid.
[0067] Example 2: This example is used to illustrate the applicability of the preparation method of the present invention for scale-up preparation.
[0068] 2.0 g of polysorbate 80 was added to 5000 g of coolant base solution and stirred until homogeneous. Then, 2.5 g of multi-walled carbon nanotubes were added, stirred for 10 min, and then ultrasonically homogenized for 20 min at a power of 1.0 kW and a frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 25.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 120 min at a power of 2.0 kW and a frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.5 g of nano-alumina and 2.5 g of hydroxypropyl methylcellulose were added to the obtained system, stirred for 20 min, and then ultrasonically homogenized for another 20 min at a power of 0.5 kW and a frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0069] The thermal conductivity of the graphene coolant was measured to be 0.4403 W / (m·K), and the viscosity was 2.87 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4404 W / (m·K), and the viscosity was 2.87 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4401 W / (m·K), and the viscosity was 2.88 mPa·s. The thermal conductivity of the obtained graphene coolant increased by approximately 10.5%, and the viscosity increased by approximately 3.2%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 99.5%. Compared with Example 1, Example 2 is a graphene coolant obtained under scale-up preparation conditions. Its thermal conductivity, viscosity, and thermal conductivity recovery rate after standing and redispersing are basically the same, indicating that the preparation method has a certain scale-up applicability. Further measurement showed that the absolute value of the Zeta potential of the graphene coolant obtained in this example was 38.1 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The convective heat transfer coefficient under laminar flow conditions was increased by about 20.7% compared with the same ethylene glycol / water coolant base liquid.
[0070] Example 3: This example illustrates that acetylenic diol polyoxyethylene ether, tannic acid, and polyvinylpyrrolidone can be used for in-situ exfoliation and dispersion of graphite, and also demonstrates the enhanced thermal conductivity of the graphene coolant obtained under conditions of higher thermally conductive filler content.
[0071] 0.5 g of acetylacetonate diol polyoxyethylene ether and 7.5 g of tannic acid were added to 5000 g of coolant base solution and stirred until homogeneous. Then, 10.0 g of multi-walled carbon nanotubes were added, and the mixture was stirred for 15 min, followed by ultrasonic homogenization for 30 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a homogeneous dispersion. Subsequently, 100.0 g of expanded graphite was added to the above homogeneous dispersion, and the mixture was stirred until homogeneous. Then, ultrasonic in-situ exfoliation was performed for 180 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 2.0 g of nano-alumina and 10.0 g of polyvinylpyrrolidone were added to the obtained system, and the mixture was stirred for 20 min, followed by ultrasonic homogenization for another 30 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled at 10-20℃ during the ultrasonication process.
[0072] The thermal conductivity of the graphene coolant was measured to be 0.5193 W / (m·K), and the viscosity was 3.50 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.5191 W / (m·K), and the viscosity was 3.51 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.5190 W / (m·K), and the viscosity was 3.50 mPa·s. The obtained graphene coolant showed an increase in thermal conductivity of approximately 30.3% and a viscosity increase of approximately 25.9%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 99.8%. Compared with Example 1, Example 3 had a higher amount of graphite powder and carbon nanotubes added, resulting in a more significant increase in thermal conductivity, but the system viscosity also increased accordingly. Further measurements showed that the absolute value of the Zeta potential of the graphene coolant obtained in this example was 41.6 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The convective heat transfer coefficient of the obtained graphene coolant under laminar flow conditions was increased by about 47.5% compared with the same ethylene glycol / water coolant base liquid.
[0073] Example 4: This example illustrates the effect of octylphenol polyoxyethylene ether (Triton X-100) as a stripping aid for in-situ stripping and dispersion of graphite.
[0074] 0.6 g of Triton X-100 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 10 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a homogeneous dispersion. Subsequently, 5.0 g of expanded graphite was added to the above homogeneous dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 30 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.1 g of nano-alumina and 0.5 g of hydroxypropyl methylcellulose were added to the obtained system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0075] The thermal conductivity of the graphene coolant was measured to be 0.4439 W / (m·K), and the viscosity was 2.94 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4436 W / (m·K), and the viscosity was 2.93 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4437 W / (m·K), and the viscosity was 2.94 mPa·s. The obtained graphene coolant showed an increase in thermal conductivity of approximately 11.4% and an increase in viscosity of approximately 5.8%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 99.6%. Furthermore, the absolute value of the Zeta potential of the graphene coolant obtained in this example was measured to be 36.3 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The obtained graphene coolant showed that the convective heat transfer coefficient under laminar flow conditions was about 23.5% higher than that of the same ethylene glycol / water coolant base liquid.
[0076] Example 5: This example illustrates that sodium diisobutylnaphthalenesulfonate and sodium naphthalenesulfonate formaldehyde polymer can be used for in-situ exfoliation and dispersion of graphite.
[0077] 0.1 g of acetylacetonate diol polyoxyethylene ether and 0.3 g of sodium diisobutylnaphthalene sulfonate were added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 10 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 5.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 30 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.1 g of nano-alumina and 0.7 g of sodium naphthalene sulfonate formaldehyde polymer were added to the obtained system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0078] The thermal conductivity of the graphene coolant was measured to be 0.4477 W / (m·K), and the viscosity was 3.02 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4479 W / (m·K), and the viscosity was 3.01 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4473 W / (m·K), and the viscosity was 3.02 mPa·s. The obtained graphene coolant showed an increase in thermal conductivity of approximately 12.3% and a viscosity increase of approximately 8.6%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 99.2%. Furthermore, the absolute value of the Zeta potential of the graphene coolant obtained in this embodiment was measured to be 39.9 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The convective heat transfer coefficient of the obtained graphene coolant under laminar flow conditions was increased by about 25.0% compared with the same ethylene glycol / water coolant base liquid.
[0079] Example 6: This example illustrates that boron nitride nanoparticles can be used as inorganic nanoparticle additives for structural control of composite thermal conductive systems.
[0080] 0.1 g of acetylacetonate diol polyoxyethylene ether and 1.5 g of tannic acid were added to 1000 g of coolant base solution and stirred until homogeneous. Then, 3.0 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 20 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 20.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 120 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.4 g of boron nitride nanoparticles and 2.0 g of hydroxypropyl methylcellulose were added to the obtained system, stirred for 20 min, and then ultrasonically homogenized for another 20 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0081] The thermal conductivity of the graphene coolant was measured to be 0.5243 W / (m·K), and the viscosity was 3.62 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.5246 W / (m·K), and the viscosity was 3.59 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.5245 W / (m·K), and the viscosity was 3.60 mPa·s. The obtained graphene coolant showed an increase in thermal conductivity of approximately 31.6% and a viscosity increase of approximately 30.2%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 100.0%. Furthermore, the absolute value of the Zeta potential of the graphene coolant obtained in this embodiment was measured to be 36.3 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The convective heat transfer coefficient of the obtained graphene coolant under laminar flow conditions was increased by about 51.3% compared with the same ethylene glycol / water coolant base liquid.
[0082] Example 7: This example illustrates that high-pressure homogenization can replace ultrasonic treatment in step S2 for in-situ graphite exfoliation.
[0083] 0.1 g of acetylacetonate diol polyoxyethylene ether and 1.5 g of tannic acid were added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 15 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 5.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then subjected to high-pressure homogenization treatment for in-situ exfoliation and dispersion at a pressure of 100 MPa for 5 cycles, with a mechanical energy input per unit volume of 0.1-1.5 kWh / L, forming a graphene-carbon nanotube composite dispersion system. Then, 0.1 g of nano-alumina and 0.5 g of hydroxypropyl methylcellulose were added to the obtained system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature during the above treatment was 10-40℃.
[0084] The thermal conductivity of the graphene coolant was measured to be 0.4511 W / (m·K), and the viscosity was 2.90 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4507 W / (m·K), and the viscosity was 2.91 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4511 W / (m·K), and the viscosity was 2.89 mPa·s. The thermal conductivity of the obtained graphene coolant increased by approximately 13.2%, and the viscosity increased by approximately 4.3%. The thermal conductivity after standing for 30 days and then redispersing essentially recovered to the initial level, with a recovery rate of approximately 100.0%. Furthermore, the absolute value of the Zeta potential of the graphene coolant obtained in this embodiment was measured to be 39.3 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat exchange test device. The convective heat transfer coefficient of the obtained graphene coolant under laminar flow conditions was increased by about 26.1% compared with the same ethylene glycol / water coolant base liquid.
[0085] The main formulations and preparation process parameters of the graphene coolants in Examples 1-7 above are shown in Table 1, and the performance tests are shown in Table 2.
[0086] Table 1. Main formulations and process parameters for Examples 1-7
[0087] sample base liquid / g Peeling aid CNTs / g Graphite / g Inorganic nano-additives Dispersing agents Main stripping / homogenization conditions Example 1 1000 Polysorbate 80 0.2 g 0.5 5 0.1 g of nano-alumina HPMC 0.5 g CNTs were sonicated for 10 min; graphite was sonicated for 30 min; followed by homogenization for 5 min. Example 2 5000 Polysorbate 80 2.0 g 2.5 25 0.5 g of nano-alumina HPMC 2.5 g CNTs were sonicated for 20 min; graphite was sonicated for 120 min; followed by homogenization for 20 min. Example 3 5000 0.5 g of acetylacetonate diol polyoxyethylene ether + 7.5 g of tannic acid 10 100 Nano-alumina 2.0 g PVP 10.0 g CNTs were sonicated for 30 min; graphite was sonicated for 180 min; followed by homogenization for 30 min. Example 4 1000 Triton X-100 0.6 g 0.5 5 0.1 g of nano-alumina HPMC 0.5 g CNTs were sonicated for 10 min; graphite was sonicated for 30 min; followed by homogenization for 5 min. Example 5 1000 0.1 g of acetylacetonate diol polyoxyethylene ether + 0.3 g of sodium diisobutylnaphthalene sulfonate 0.5 5 0.1 g of nano-alumina Sodium salt of naphthalenesulfonic acid formaldehyde polymer 0.7 g CNTs were sonicated for 10 min; graphite was sonicated for 30 min; followed by homogenization for 5 min. Example 6 1000 0.1 g of acetylacetonate diol polyoxyethylene ether + 1.5 g of tannic acid 3 20 0.4 g of nano boron nitride HPMC 2.0 g CNTs were sonicated for 20 min; graphite was sonicated for 120 min; followed by homogenization for 20 min. Example 7 1000 0.1 g of acetylacetonate diol polyoxyethylene ether + 1.5 g of tannic acid 0.5 5 0.1 g of nano-alumina HPMC 0.5 g CNTs were sonicated for 15 min; graphite was homogenized 5 times under 100 MPa high pressure; then homogenized for 5 min.
[0088] Note: HPMC is hydroxypropyl methylcellulose, and PVP is polyvinylpyrrolidone; the ultrasonic frequency in each example is 20kHz, and the system temperature is controlled at 10-40℃, with Example 3 controlled at 10-20℃.
[0089] Table 2. Thermal conductivity, rheological properties, recovery properties, and heat transfer properties of the graphene coolants obtained in Examples 1-7
[0090] sample initial value k = W / (m·K) k (after resting and redispersing) W / (m·K) k Initial boost rate / % Viscosity mPa·s Viscosity growth rate / % 30-day thermal conductivity recovery rate (%) Zeta potential / mV Convection heat transfer coefficient improvement rate / % Example 1 0.4391 0.4388 10.2 2.86 2.8 99.3 45.0 20.2 Example 2 0.4403 0.4401 10.5 2.87 3.2 99.5 38.1 20.7 Example 3 0.5193 0.519 30.3 3.5 25.9 99.8 41.6 47.5 Example 4 0.4439 0.4437 11.4 2.94 5.8 99.6 36.3 23.5 Example 5 0.4477 0.4473 12.3 3.02 8.6 99.2 39.9 25.0 Example 6 0.5243 0.5245 31.6 3.62 30.2 100.0 36.3 51.3 Example 7 0.4511 0.4511 13.2 2.9 4.3 100 39.3 26.1
[0091] Note: The thermal conductivity of the same ethylene glycol / water coolant base is 0.3985 W / (m·K), and the dynamic viscosity at 25 ℃ is 2.78 mPa·s.
[0092] Example 8: As Figure 3 As shown, the graphene coolant with reversible recovery properties obtained in Example 1 was allowed to stand at room temperature for 48 hours to form an upper stable dispersion layer and a lower reversible enrichment layer. The upper stable dispersion layer was separated and taken to obtain a stable dispersion type graphene coolant. The obtained upper stable dispersion layer has a uniform appearance and can be used for cold plate circulating heat exchange or thermal conductivity testing. The lower reversible enrichment layer and all the separated upper stable dispersion layers were remixed and then subjected to artificial vibration, mechanical stirring at 100-200 rpm for 5-10 min, circulating pumping for 1-10 min, or low-intensity ultrasonic treatment to redisperse the system in the coolant base liquid, forming a redispersible system with a uniform appearance.
[0093] Comparative Example 1: This comparative example is used to illustrate that when commercial graphene powder is directly added, its redispersibility and thermal conductivity enhancement retention in the coolant base liquid are weaker than those of the in-situ exfoliation method.
[0094] 0.2 g of polysorbate 80 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 10 min at a power of 1.0 kW and a frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 5.0 g of commercial graphene powder was added to the above uniform dispersion, stirred for 10 min, and then ultrasonically dispersed for 30 min at a power of 2.0 kW and a frequency of 20 kHz. Then, 0.1 g of nano-alumina and 0.5 g of hydroxypropyl methylcellulose were added to the resulting system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at a power of 0.5 kW and a frequency of 20 kHz to obtain a control coolant. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0095] The thermal conductivity of the comparative coolant was measured to be 0.4372 W / (m·K), and its viscosity was 2.84 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4312 W / (m·K), and the viscosity was 2.81 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4214 W / (m·K), and the viscosity was 2.83 mPa·s. The initial thermal conductivity of this comparative coolant increased by approximately 9.7%, and the viscosity increased by approximately 2.2%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was approximately 59.17%. Further measurement showed that the absolute value of the Zeta potential of the graphene coolant obtained in this comparative example was 24.8 mV, indicating that the dispersion stabilizing effect of the graphene coolant was relatively insufficient. As shown in Table 3, compared with Example 1, commercial graphene powder is prone to sheet stacking and agglomeration during preparation, drying and storage. It is more difficult to re-wet and redisperse in ethylene glycol / water coolant base liquid. After standing, it is easy to form a sedimentation layer that is difficult to reopen. This indicates that the method of in-situ exfoliation of graphite in coolant base liquid of the present invention is beneficial to improving the compatibility and reversible recovery performance of graphene with the target medium.
[0096] Comparative Example 2: This comparative example is used to illustrate that without the addition of carbon nanotubes, the graphene sheets lack one-dimensional bridging and supporting structures, resulting in a decrease in the ability to construct composite thermally conductive structures.
[0097] 0.2 g of polysorbate 80 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 5.0 g of expanded graphite was added, and the mixture was stirred for 10 min, followed by in-situ ultrasonic exfoliation for 30 min at a power of 2.0 kW and a frequency of 20 kHz to form a graphene dispersion system. Next, 0.1 g of nano-alumina and 0.5 g of hydroxypropyl methylcellulose were added to the resulting system, and the mixture was stirred for 10 min, followed by ultrasonic homogenization for 5 min at a power of 0.5 kW and a frequency of 20 kHz to obtain a control coolant. The system temperature was controlled between 10 and 40 °C during the ultrasonication process.
[0098] The thermal conductivity of the comparative coolant was measured to be 0.4248 W / (m·K), and its viscosity was 2.82 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4128 W / (m·K), and the viscosity was 2.82 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4031 W / (m·K), and the viscosity was 2.82 mPa·s. The thermal conductivity of this comparative coolant increased by approximately 6.6%, and the viscosity increased by approximately 1.4%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was 17.5%. Further measurement showed that the absolute value of the Zeta potential of the graphene coolant obtained in this comparative example was 19.4 mV, indicating that the dispersion stabilizing effect of the graphene coolant was relatively insufficient. As shown in Table 3, compared with Example 1, no carbon nanotubes were added in this comparative example. The initial viscosity of the system was lower, but the increase in thermal conductivity was significantly reduced. Moreover, the enhanced thermal conductivity was difficult to recover after standing. This indicates that the bridging, supporting and connecting effects of carbon nanotubes between graphene sheets help to construct a recoverable one-dimensional-two-dimensional composite thermal conductive structure.
[0099] Comparative Example 3: This comparative example is used to illustrate that the lamellar spacing and structural regulation of the composite dispersion system are insufficient when no inorganic nano-additives are added.
[0100] 0.2 g of polysorbate 80 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 10 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a homogeneous dispersion. Subsequently, 5.0 g of expanded graphite was added to the above homogeneous dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 30 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.5 g of hydroxypropyl methylcellulose was added to the obtained system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a control coolant.
[0101] The thermal conductivity of the comparative coolant was measured to be 0.4315 W / (m·K), and the viscosity was 2.84 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4310 W / (m·K), and the viscosity was 2.85 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4312 W / (m·K), and the viscosity was 2.84 mPa·s. The thermal conductivity of this comparative coolant increased by approximately 8.3%, and the viscosity increased by approximately 2.2%; the thermal conductivity recovery rate after standing for 30 days and then redispersing was 99.1%. Furthermore, the absolute value of the Zeta potential of the graphene coolant obtained in this comparative example was measured to be 37.1 mV, indicating that the graphene coolant formed a relatively stable composite dispersion structure. The dynamic heat transfer performance under laminar flow conditions was further evaluated using a cold plate circulating heat transfer test device. The obtained graphene coolant showed an approximately 12.3% increase in convective heat transfer coefficient under laminar flow conditions compared to the same ethylene glycol / water coolant base. As shown in Table 3, compared to Example 1, this comparative example did not include nano-alumina, and the increase in thermal conductivity and convective heat transfer coefficient of the obtained coolant was less than that in Example 1. This result indicates that inorganic nano-additives can help improve the thermal conductivity enhancement and cold plate heat transfer capability of the composite thermal conductive system.
[0102] Comparative Example 4: This comparative example is used to illustrate the changes in the stable dispersion and reversible recovery ability of the graphene-carbon nanotube composite system without the addition of dispersing agents.
[0103] 0.2 g of polysorbate 80 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 10 min at an ultrasonic power of 1.0 kW and an ultrasonic frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 5.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 30 min at an ultrasonic power of 2.0 kW and an ultrasonic frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.1 g of nano-alumina was added to the obtained system without adding any dispersing aids, stirred for 10 min, and then ultrasonically homogenized for another 5 min at an ultrasonic power of 0.5 kW and an ultrasonic frequency of 20 kHz to obtain a control coolant. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0104] The thermal conductivity of the comparative coolant was measured to be 0.4132 W / (m·K), and its viscosity was 3.21 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4075 W / (m·K), and the viscosity was 3.23 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4071 W / (m·K), and the viscosity was 3.22 mPa·s. The initial thermal conductivity of this comparative coolant increased by approximately 3.7%, and the viscosity increased by approximately 15.5%. Further measurement showed that the absolute value of the Zeta potential of the graphene coolant obtained in this comparative example was 18.7 mV, indicating that the dispersion stabilizing effect of the graphene coolant was relatively insufficient. As shown in Table 3, compared with Example 1, this comparative example did not contain any dispersing aids, resulting in severe agglomeration and an increased initial viscosity. The results show that dispersants can improve the reversible dispersion recovery performance of graphene / carbon nanotube composite systems through adsorption, entanglement or steric hindrance, so that the system can still recover its thermal conductivity after standing by light stirring, shaking or circulating pumping.
[0105] Comparative Example 5: This comparative example is used to illustrate that when the carbon nanotube untangling and in-situ graphite exfoliation time is short, insufficient graphite exfoliation and dispersion will affect the system performance.
[0106] 0.2 g of polysorbate 80 was added to 1000 g of coolant base solution and stirred until homogeneous. Then, 0.5 g of multi-walled carbon nanotubes were added, stirred for 5 min, and then ultrasonically homogenized for 5 min at a power of 1.0 kW and a frequency of 20 kHz to obtain a uniform dispersion. Subsequently, 5.0 g of expanded graphite was added to the above uniform dispersion, stirred until homogeneous, and then ultrasonically exfoliated in situ for 20 min at a power of 2.0 kW and a frequency of 20 kHz to form a graphene-carbon nanotube composite dispersion system. Then, 0.1 g of nano-alumina and 0.5 g of hydroxypropyl methylcellulose were added to the obtained system, stirred for 10 min, and then ultrasonically homogenized for another 5 min at a power of 0.5 kW and a frequency of 20 kHz to obtain a graphene coolant with reversible recovery properties. The system temperature was controlled between 10-40℃ during the ultrasonication process.
[0107] The thermal conductivity of the graphene coolant was measured to be 0.4103 W / (m·K), and the viscosity was 5.22 mPa·s. After standing for 15 days and then redispersing, the thermal conductivity was 0.4098 W / (m·K), and the viscosity was 5.23 mPa·s. After standing for 30 days and then redispersing, the thermal conductivity was 0.4101 W / (m·K), and the viscosity was 5.23 mPa·s. The thermal conductivity of the obtained graphene coolant increased by approximately 2.9%, and the viscosity increased by approximately 87.8% compared to the base liquid. As shown in Table 3, compared with Example 1, the time for carbon nanotube unwrapping and in-situ graphite exfoliation was insufficient, resulting in poor material layer exfoliation and dispersion effects, and a large number of particles agglomerated within the system, ultimately leading to a higher viscosity of the coolant and a decreased increase in the thermal conductivity. Further measurement showed that the absolute value of the Zeta potential of the graphene coolant obtained in this comparative example was 29.3 mV, indicating that the dispersion stabilizing effect of the graphene coolant was relatively insufficient.
[0108] Table 3 Performance comparison between Example 1 and Comparative Examples 1-5
[0109] sample Main differences Initial thermal conductivity W / (m·K) Thermal conductivity of redispersion over 30 days (W / (m·K)) Initial thermal conductivity improvement rate / % 30-day thermal conductivity recovery rate / % Zeta potential / mV Example 1 In-situ exfoliation + CNTs + dispersing agent + nano alumina 0.4391 0.4388 10.2 99.3 45.0 Comparative Example 1 Commercial graphene powder 0.4372 0.4214 9.7 59.2 24.8 Comparative Example 2 Without CNT 0.4248 0.4031 6.6 17.5 19.4 Comparative Example 3 Without nano-alumina 0.4315 0.4312 8.3 99.1 37.1 Comparative Example 4 No dispersing agent added 0.4132 0.4071 3.7 / 18.7 Comparative Example 5 Low mechanical energy input 0.4103 0.4101 2.9 / 29.3
[0110] Reference Example 1: This reference example illustrates that expanded graphite can form multilayer graphene nanosheets in a coolant base fluid after in-situ ultrasonic exfoliation. Compared to Example 1, this reference example does not include carbon nanotubes or inorganic nano-auxiliaries during the preparation process and is mainly used for characterizing the layered structure.
[0111] 0.2 g of polysorbate 80 was added to 1000 g of coolant base liquid and stirred until homogeneous. Then, 5.0 g of expanded graphite was added, and the mixture was stirred for 10 min, followed by in-situ ultrasonic exfoliation for 30 min at a power of 2.0 kW and a frequency of 20 kHz to form a graphene dispersion system. Next, 0.5 g of hydroxypropyl methylcellulose was added to the resulting system, and the mixture was stirred for 10 min, followed by ultrasonic homogenization for 5 min at a power of 0.5 kW and a frequency of 20 kHz. The system temperature was controlled between 10-40℃ during ultrasonication. The resulting graphene coolant was allowed to stand for 48 h for fractionation treatment. The upper stable dispersion layer was taken as the stable dispersion graphene coolant and used for thermal conductivity, viscosity, and AFM testing.
[0112] The thermal conductivity of the graphene coolant was measured to be 0.4228 W / (m·K), and the viscosity was 2.92 mPa·s. After standing for 15 days, the thermal conductivity was 0.4223 W / (m·K), and the viscosity was 2.91 mPa·s. After standing for 30 days and redispersing, the thermal conductivity was 0.4227 W / (m·K), and the viscosity was 2.91 mPa·s. The obtained graphene coolant showed an increase in thermal conductivity of approximately 6.1% and a viscosity increase of approximately 5.0%; the thermal conductivity recovery rate after standing for 30 days and redispersing was approximately 99.6%. Further measurement showed that the absolute value of the Zeta potential of the graphene coolant obtained in this reference example was 49.2 mV, indicating that larger particles, easily settled sheets, and some agglomerated structures in the system had been removed, hence its high absolute Zeta potential. Figure 2 As shown, the AFM test results indicate that the average thickness of the sheet material in the obtained coolant is 20.0 nm, indicating that expanded graphite was exfoliated in situ by ultrasonication to form graphene nanosheets.
[0113] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.
Claims
1. A method for preparing a graphene coolant with reversible recovery properties, characterized in that, Includes the following steps: The stripping agent and carbon nanotubes were added to the coolant base liquid, and after stirring and dispersion homogenization, a uniform dispersion was obtained. Graphite raw material is added to the uniform dispersion liquid, and after stirring and dispersion homogenization treatment, the graphite raw material is directly exfoliated in situ in the cooling liquid base liquid to form graphene nanosheets, and at the same time, the graphene nanosheets and carbon nanotubes form a graphene-carbon nanotube composite dispersion system in the cooling liquid base liquid. Inorganic nano-auxiliaries and dispersing agents are added to the graphene-carbon nanotube composite dispersion system, and after stirring and dispersion homogenization, a graphene coolant with reversible recovery properties is obtained; the inorganic nano-auxiliaries are used as layer spacer components or reversible enrichment layer structure regulating components. The reversible recovery performance refers to the ability of the graphene coolant to reform into a uniform dispersion system after settling, stratification, or soft agglomeration under the action of mechanical external force, and the thermal conductivity recovery rate of the redispersed graphene coolant calculated according to the thermal conductivity enhancement recovery rate is not less than 99.0%.
2. The method for preparing the graphene coolant with reversible recovery properties according to claim 1, characterized in that, The coolant base is a water mixture of one or more of the following: ethylene glycol, propylene glycol, glycerin, diethylene glycol, and triethylene glycol.
3. The method for preparing the graphene coolant with reversible recovery properties according to claim 1, characterized in that, The graphite raw material is one or more of expandable graphite, expanded graphite, and flake graphite, with a mesh size <80 mesh and a carbon content >99%; the amount of graphite raw material added accounts for 0.05-5.0 wt% of the total mass of the graphene coolant; the carbon nanotubes are one or more of multi-walled carbon nanotubes and functionalized carbon nanotubes, with an outer diameter distribution of 5-20 nm, a carbon tube length of 1-30 μm, and a carbon content >99%; the amount of carbon nanotubes added accounts for 0.001-0.5 wt% of the total mass of the graphene coolant.
4. The method for preparing the graphene coolant with reversible recovery properties according to claim 1, characterized in that, The stripping agent is one or more of the following: sodium pyrene tetrasulfonate, sodium diisobutylnaphthalene sulfonate, tannic acid, octylphenol polyoxyethylene ether, polysorbate, fatty alcohol polyoxyethylene ether, and acetylenol wetting agents; the dispersing agent is one or more of the following: polyvinylpyrrolidone, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, branched polyester, polyvinyl alcohol, polyacrylate, sodium naphthalene sulfonate formaldehyde polymer, quaternary ammonium salt polymer, and block polyether dispersants; the amount of the stripping agent and the dispersing agent added is independently 0.001-2.5 wt% of the total mass of the graphene coolant.
5. The method for preparing the graphene coolant with reversible recovery properties according to claim 1, characterized in that, The inorganic nano-additive is one or more of nano-silica, nano-alumina, nano-boron nitride, nano-magnesium oxide, nano-zinc oxide, nano-copper oxide, and nano-titanium dioxide; the amount of the inorganic nano-additive is 0.001-1.0 wt% of the total mass of the graphene coolant; the inorganic nano-additive is added after the graphene-carbon nanotube composite dispersion system is formed and distributed between graphene nanosheets or in the graphene-carbon nanotube composite structure, which is used to reduce the density of the graphene nanosheets and keep the enriched structure formed after standing in a redispersible state; at the same time, the inorganic nano-additive is used to improve the interfacial wetting and thermal coupling between the composite dispersion system and the coolant base liquid, and improve the effective thermal conductivity of the near-wall region of the cold plate.
6. The method for preparing the graphene coolant with reversible recovery properties according to claim 1, characterized in that, The dispersion homogenization process is independently one or more of the following: ultrasonic homogenization, high-pressure homogenization, microfluidic treatment, cell disruption homogenization, or sand milling homogenization. The ultrasonic homogenizer has a power of 0.2-5.0 kW, an ultrasonic frequency of 10-60 kHz, and an ultrasonic energy input of not less than 0.005-0.1 kWh / L. The working pressure of the high-pressure homogenizer is 60-150 MPa, and the cycle is 1-20 times. The working pressure of the microjet treatment is 30-250 MPa, and the treatment is repeated 1-15 times. The working pressure for cell disruption and homogenization is 20-180 MPa, and the process is repeated 1-15 times. The grinding media used in the sand milling process has a particle size of 0.05-1.0 mm, a grinding media filling rate of 50%-90%, a rotation speed of 1000-5000 rpm, and a processing time of 10-180 min. The system operating temperature during the dispersion and homogenization process shall not exceed 60℃.
7. The method for preparing the graphene coolant with reversible recovery properties according to any one of claims 1-6, characterized in that, The preparation method further includes a static grading step; the static grading step includes: allowing the graphene coolant to stand, so that the system forms an upper stable dispersion layer and a lower reversible enrichment layer, separating and taking the upper stable dispersion layer to obtain a stable dispersion graphene coolant; the static grading time is 8-48 h; the lower reversible enrichment layer is a soft agglomerate or redispersible enrichment structure containing graphene nanosheets, carbon nanotubes, inorganic nano-auxiliaries and dispersing agents.
8. The method for preparing the graphene coolant with reversible recovery properties according to claim 7, characterized in that, After the lower reversible enrichment layer is recombined with all the separated upper stable dispersion layers, it is stirred, oscillated or circulated and pumped to restore the appearance of a uniform dispersion system with the same composition as before standing and grading; the thermal conductivity recovery rate of the redispersed system calculated according to the thermal conductivity enhancement recovery rate is not less than 99.0%.
9. A graphene coolant with stable dispersion or reversible recovery properties prepared by any one of the preparation methods described in claims 1-8.
10. The application of the graphene coolant as described in claim 9 as a liquid cooling heat dissipation medium.
Citation Information
Patent Citations
Nano-fluid for efficient heat transfer fluid, preparation method thereof and heat exchange device
CN109384219A
Composition for preparing graphene nanofluid cooling liquid, graphene nanofluid cooling liquid as well as preparation method and application of graphene nanofluid cooling liquid
CN119823728A
Preparation method of graphene cooling liquid for liquid-cooled radiator
CN121674036A